Is there a bank lending channel in Hungary? Evidence from bank panel data - Csilla Horváth; Judit Krekó; Anna Naszódi (Magyar Nemzeti Bank, 2006)
In this paper we analyze the bank lending channel in Hungary. We provide a brief overview of the theory and the empirical approaches used to investigate the existence of bank lending channel. From the possible methods we use the generally applied approach suggested by Kahsyap and Stein (1995) which relies on discovering asymmetries in changes in the amount of loans to monetary actions in order to isolate supply and demand effects. We estimate an ARDL model where the asymmetric effects are captured by interaction-terms. We find significant asymmetric adjustment of loan quantities along certain bank characteristics. The existence of bank lending channel, and therefore loan supply decisions of banks, can explain these asymmetries. In addition, we do not find any sign for asymmetric loan demand adjustment along these variables. According to these findings, we cannot rule out the existence of the bank lending channel in Hungary.
Keywords: C23; E44; E52; G21; 330; monetary transmission; credit channel; bank lending channel; ARDL model; Geldpolitische Transmission; Geldpolitische Transmission; Ungarn